Application of Dye‐coated Ultrasmall Gadolinium Oxide Nanoparticles for Biomedical Dual Imaging. (16th August 2017) - Miao, Xu; Xu, Wenlong; Cha, Hyunsil; Chang, Yongmin; Oh, In Taek; Chae, Kwon Seok; Lee, Gang Ho
Abstract : Nanoparticles are very important in biomedical imaging because their imaging properties are superior to those of small molecules. They can be further functionalized for multimodal imaging through surface modification. In this study, we synthesized dye‐coated ultrasmall gadolinium oxide nanoparticles [dye = fluorescein and fluorescein isothiocyanate (FITC)] in one‐pot and investigated their dual imaging properties. The dye‐coated gadolinium oxide nanoparticles exhibited excellent relaxometric properties suitable for T1 magnetic resonance imaging (MRI): r1 = 9.8 s −1 mM −1 ( r 2 / r 1 = 2.6) for fluorescein‐coated nanoparticles ( d avg = 1.6 ± 0.1 nm) and r1 = 12.3 s −1 mM −1 ( r 2 / r 1 = 2.3) for FITC‐coated nanoparticles ( d avg = 1.4 ± 0.1 nm), and strong photoluminescence (PL) in the green region (around 514 nm) suitable for fluorescent imaging (FI). The dye‐coated nanoparticles exhibited strong fluorescence in cellular confocal images and high contrast in T1 MR images in mice, suggesting that they are potential dual T1 MRI‐FI agents. Abstract :